1975
DOI: 10.1099/00221287-88-1-49
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of Antibiotic Resistance Plasmid RP1 into Pseudomonas glycinea and Pseudomonas phaseolicola in vitro and in planta

Abstract: The wide host-range antibiotic resistance plasmid RPI was transferred from Pseudomonas aeruginosa via Escherichia coli into Pseudomonas glycinea. The plasmid was then acquired by Pseudomonas phaseolicola both in vitro and in planta in Phaseolus limensis leaves and pods. This was the first step in the design of a model system to determine the possible epidemiological significance of antibiotic resistance plasmids in the control of plant disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
1

Year Published

1983
1983
2003
2003

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 18 publications
1
15
1
Order By: Relevance
“…gbcinea to P. yringae pv. pbaseolicola in the phylloplane of bean was reported during the first 4 h after inoculation with an excess of donors (Lacy & Leary, 1975). Likewise, during the first hours after inoculation, P. syringae pv.…”
Section: Conjugal Transfer To Indigenous Bacteria In Plantamentioning
confidence: 90%
See 1 more Smart Citation
“…gbcinea to P. yringae pv. pbaseolicola in the phylloplane of bean was reported during the first 4 h after inoculation with an excess of donors (Lacy & Leary, 1975). Likewise, during the first hours after inoculation, P. syringae pv.…”
Section: Conjugal Transfer To Indigenous Bacteria In Plantamentioning
confidence: 90%
“…tomato contain conjugative plasmids (Bender & Cooksey, 1986 ;Powell e t al., 1993). High frequencies of conjugation between added donors and recipients on the leaf surface and in the leaf tissue have been reported (Lacy & Leary, 1975;Lacy e t al., 1984;Manceau et al, 1986).…”
Section: Introductionmentioning
confidence: 97%
“…versity of Michigan, Ann Arbor, MI 48104), has Further, in in vitro experiments, plasmids carrybeen used in previous studies (12,14). ing genes mediating resistance to tetracyclines, as Spontaneous mutants to OTC resistance.…”
Section: High Levels Of Streptomycin Resistance In Ementioning
confidence: 99%
“…The rapid increase of these drug-resistant bacteria in agricultural fields including orchards and nurseries could be caused by plasmid-mediated transfer of drug-resistance genes among bacterial strains because most of these genes are encoded by native plasmids of plant pathogenic bacteria (Burr et al 1988;Cazorla et al 2002;Chiou and Jones 1991;Cooksey et al 1990;Minsavage et al 1990;Nakajima et al 2002;Sundin and Bender 1993). However, there is no information about in planta transfer of these native plasmids between bacterial strains on the phylloplane, although that of the nonnative plasmid, including RP1 (Lacy and Leary 1975), RSF1010 (Sato et al 1982), and transposon-inserted plasmid (pBPW1::Tn7), (Sato 1988;Sato et al 1985) has been reported.…”
Section: Introductionmentioning
confidence: 97%